2002
DOI: 10.1046/j.1365-2486.2002.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of elevated CO2 and temperature on the leaf‐miner Dialectica scalariella Zeller (Lepidoptera: Gracillariidae) in Paterson's Curse, Echium plantagineum (Boraginaceae)

Abstract: Doubling of the current atmospheric CO2 concentration, and an increase in global mean annual temperatures of 1.5–6 °C, have been predicted to occur by the end of this century. Whilst the separate effects of CO2 and temperature on plant–insect interactions have been examined in a number of studies, few have investigated their combined impact. We carried out a factorial experiment to explore the effect of a doubling of CO2 concentration and a 3 °C temperature increase on the development of a complete generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 39 publications
(57 reference statements)
2
65
2
Order By: Relevance
“…miners) may well be affected by elevated CO 2 -induced reductions in foliage quality and an elevated growth temperature in other ways. In an herbaceous plant system, declines in leaf quality at elevated CO 2 dampened the effects of more rapid development of larvae at an elevated temperature (Johns and Hughes 2002). Our observed reduction in development time supports one of our original predictions, i.e.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…miners) may well be affected by elevated CO 2 -induced reductions in foliage quality and an elevated growth temperature in other ways. In an herbaceous plant system, declines in leaf quality at elevated CO 2 dampened the effects of more rapid development of larvae at an elevated temperature (Johns and Hughes 2002). Our observed reduction in development time supports one of our original predictions, i.e.…”
Section: Discussionsupporting
confidence: 86%
“…We observed little effect on insect performance during a 3-to 6-day feeding period. Although the aforementioned studies on whole leaf-feeding insects demonstrate no interactive effects of CO 2 and temperature, a study with a leaf mining insect feeding on a herbaceous plant species demonstrated that CO 2 enrichment and elevated temperature can interactively negatively impact larval survivorship and adult weight (Johns and Hughes 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Murray et al (2013a) observed that the direct positive effect of temperature was able to ameliorate the negative indirect effect of C E on insect performance. Johns and Hughes (2002) observed a partial mitigation of C Einduced plant-mediated effects as a result of direct temperature effects. In our study, no interactive effects of C E × T E were observed with P. atomaria; although developmental time was reduced as a direct result of T E , it did not compensate fully for the increased developmental time attributed to the plant-mediated effects at C E .…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have shown the importance of tritrophic interactions when evaluating the effect of environmental changes (e.g. Bezemer et al, 1998;Coley, 1998;Johns and Hughes, 2002;Hamilton et al, 2004;Menéndez, 2007;Thuiller, 2007;Battisti, 2008).…”
Section: Introductionmentioning
confidence: 99%